Hubungan Optimisme dengan Resiliensi Anak dari Keluarga yang Bercerai - Osmayeni, Sisri; Taufik, Taufik (Lembaga Yasin AlSys, 2024)
Parental divorce is a source of problems and has a negative impact on many children. Children who are victims of their parents show signs of pessimism, anxiety, self-blame and feelings of insecurity. To overcome these impacts, it is important for children to develop emotional skills and resilience to face difficulties and problems, one of which can be achieved through resilience. This research aims to (1) describe the optimism of students from divorced families, (2) describe the resilience of students from divorced families, (3) determine the significant relationship between optimism and the resilience of students from divorced families. This research uses a quantitative approach with a descriptive correlational research type. The subjects in the research were 32 students from divorced families. The data collection instrument was an optimism and resilience questionnaire using a Likert scale model. Data were analyzed with the help of correlational descriptive statistics with SPSS version 26.00. The results showed that (1) the average achievement score for the level of optimism of students whose parents were divorced was 86.5 (64.7%) including the medium category and most students had a moderate level of optimism, (2) the average achievement score for the level of The resilience of students whose parents were divorced was 135 (62.8%) in the medium category and most students had a moderate level of resilience. (3) there was a positive and significant relationship between optimism and student resilience. This means that the higher the optimism, the higher the student's resilience. Based on these findings, guidance and counseling teachers in schools can make efforts to increase optimism and self-resilience through guidance and counseling services including individual counseling services, information services, group guidance services, group counseling services and content mastery services.